STUDI PENDAHULUAN PENGGUNAAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI TUMBUH KEMBANG MAKHUK HIDUP - Ranti Apriyanti; Dewi Robiatun Muharomah; Maya Rahayu (Jurnal Biogenerasi, 2026)
This Study is a preliminary study on the use of the problem ased Learning (PBL) model to improve students critical thinking skills in the subject of Gworth and Development of Living Things at SMAN 4 Kota Serang. The approach used in this study is a descriptive qualitative approach through semi-structured intervies with Biology teachers, which revealed that students critical thinking skills are still homogenous and somewhat low due to the use of conventional models. The Problem Based Laerning model is considered quite promising because it exposes students to authentic problems. Although slightly hampered by factors such as a shortage of teaching of staff and time constraints, it is necessary to conduct trials for pedadigical transformation.